Additions to a bibliography of the fauna of São Tomé e Príncipe and the island of Annobon, Gulf of Guinea. Addendum - Gascoigne, Angus (2012)
Mais 182 documentos sobre a fauna de três das quatro ilhas no Golfo de Guiné (Príncipe, São Tomé e Annobon) são apresentados.